Lowering acquisition costs with a commission cap? Evidence from the German private health insurance market - Kylie A. Braegelmann; Jörg Schiller (The Geneva Risk and Insurance Review, 2023)
When consumers are neither particularly financially literate nor price sensitive, insurers have a strong incentive to pay high commissions to intermediaries for profitable new business. As a part of cost reduction regulation in the German private substitutive health insurance market, a commission cap and a minimum cancelation liability period for insurance intermediaries were introduced in 2012. Despite the fact that the commission cap lowered commissions paid to intermediaries, we provide evidence that the reform was only partly effective, as it led to a decrease in reshuffling of new business in the substitutive market, but did not significantly reduce total acquisition costs of health insurers. Our findings confirm that cost regulation is tricky and can be easily circumvented by insurers, as commission payments are only a part of total acquisition costs.
Keywords: 330; Insurance regulation; Health insurance; Commission cap